2006
DOI: 10.1037/0096-1523.32.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood effects in reading aloud: New findings and new challenges for computational models.

Abstract: A word from a dense neighborhood is often read aloud faster than a word from a sparse neighborhood. This advantage is usually attributed to orthography, but orthographic and phonological neighbors are typically confounded. Two experiments investigated the effect of neighborhood density on reading aloud when phonological density was varied while orthographic density was held constant, and vice versa. A phonological neighborhood effect was observed, but not an orthographic one. These results are inconsistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 36 publications
6
72
1
2
Order By: Relevance
“…Reynolds and Besner (2011a) tested this prediction by conducting simulations examining how changes in the response criterion influence the effect of neighborhood density. The standard finding is that the more words that can be created by changing one letter in a letter string, the faster that string is read aloud (Adelman & Brown, 2007;Andrews, 1992;McCann & Besner, 1987;Mulatti, Reynolds, & Besner, 2006;Peereman & Content, 1995Reynolds & Besner, 2004). As was expected, increasing the response criterion in DRC so as to simulate reading aloud pseudohomophones in a pure list context yielded both a larger base word frequency effect and a larger effect of neighborhood density, as compared with lower values used to simulate when pseudohomophones and nonwords are randomly intermixed.…”
Section: A Response Criterion Accountmentioning
confidence: 80%
“…Reynolds and Besner (2011a) tested this prediction by conducting simulations examining how changes in the response criterion influence the effect of neighborhood density. The standard finding is that the more words that can be created by changing one letter in a letter string, the faster that string is read aloud (Adelman & Brown, 2007;Andrews, 1992;McCann & Besner, 1987;Mulatti, Reynolds, & Besner, 2006;Peereman & Content, 1995Reynolds & Besner, 2004). As was expected, increasing the response criterion in DRC so as to simulate reading aloud pseudohomophones in a pure list context yielded both a larger base word frequency effect and a larger effect of neighborhood density, as compared with lower values used to simulate when pseudohomophones and nonwords are randomly intermixed.…”
Section: A Response Criterion Accountmentioning
confidence: 80%
“…However, it has been shown that the phonology of words also has a considerable impact on visual word recognition. For instance, Yates, Locker, and Simpson (2004) showed that phonological neighborhood influenced visual word perception (see also Mulatti, Reynolds, & Besner, 2006). In a visual lexical decision task, participants responded more rapidly and accurately to words with larger phonological neighborhoods than to those with smaller neighborhoods.…”
mentioning
confidence: 99%
“…There has been some debate as to the nature of neighborhood density effects, because both density measures are usually strongly correlated (e.g., Mulatti, Reynolds, & Besner, 2006). Mulatti and colleagues argued that phonological neighborhood density, but not orthographic neighborhood density, affects naming performance.…”
Section: Interaction Variablesmentioning
confidence: 99%